(untitled) (Fiep Bulletin - online, 2013)
This article aims to identify the characteristics of socio-educational practitioners football society of the Mangueira Olympic Center. It was aimed to find points as the ratio of practicing soccer Olympic Project with the Mangueira school, with sports practice, its projections for the future, possible contacts with drugs and alcohol, besides suffering from exposure to firearms. Also, consider whether the role of the Mangueira Olympic Project continues to be achieved, which is helping to train young people and start them in practice sports. Our sample was formed by 86 young people aged between 7 and 16 years, with effective participation in the Olympic Project and a minimum of six months. The instrument used was a questionnaire with 15 questions directly, which was answered in the Mangueira Olympic Center and delivered soon after completion. The results were analyzed trying to understand the views and characteristics of participants, in addition to highlighting the positive points brought up by sports practice and participation in the Social Project of the Mangueira Olympic Center.